Stimulation of mitochondrial ATP synthase activity - a new diazoxide-mediated mechanism of cardioprotection - Jašová, M; Kancirová, I; Muráriková, M; Farkašová, Veronika; Waczulíková, Iveta; Ravingerová, Táňa; Ziegelhöffer, Atila; Ferko, Miroslav (Physiological research, 2016)
Pharmacological preconditioning by diazoxide and a model of experimental streptozotocin-induced acute diabetes mellitus (STZ-DM) provided similar levels of cardioprotection assessed as limiting myocardial infarct size. The aim was to explore the possibility of existence of another in vitro mechanism, which could be contributory to cardioprotection mediated by diazoxide treatment. Mitochondrial membrane fluidity and ATP synthase activity in isolated heart mitochondria were determined under the influence of two factors, STZ-DM condition and treatment with diazoxide. Both factors independently increased the ATP synthase activity (p<0.05), as no interaction effect was observed upon the combination of STZ-DM with diazoxide. On the other hand, the mitochondrial membrane fluidity was significantly increased by STZ-DM only; no significant main effect for diazoxide was found. Based on the results from measurements of enzyme kinetics, we assume a direct interaction of diazoxide with the molecule of ATP synthase stimulated its activity by noncompetitive activation. Our present work revealed, for the first time, that cardioprotection induced by diazoxide may not be caused exclusively by mitochondrial K(ATP) opening, but presumably also by a direct interaction of diazoxide with ATP synthase, although the mechanisms for achieving this activation cannot be fully delineated.
Keywords: Animals; experimentální diabetes mellitus; Rats, Wistar; Succinate Dehydrogenase; nemoci srdce; diazoxid; Heart Diseases; mitochondriální membrány; Membrane Fluidity; fluidita membrány; Mitochondrial Proton-Translocating ATPases; Male; Mitochondrial Membranes; mitochondriální protonové ATPasy; Diazoxide; mužské pohlaví; zvířata; sukcinátdehydrogenasa; potkani Wistar; Diabetes Mellitus, Experimental